Vision Correction and Eye Surgery 2022
DOI: 10.5772/intechopen.101830
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Refractive Errors after Corneal Transplantation

Abstract: Even after a successful keratoplasty with a clear graft, a high postoperative refractive error could occur too hard to correct with spectacles or contact lenses. Therefore, refractive surgery could be considered a good tool to correct these high postoperative defects. The authors showed the reasons involved in the refractive errors after successful penetrating (PKP) or lamellar transplantation (DALK), pre-, intra-, and post-operatively. Moreover, they presented different techniques to correct the refractive er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Similarly, Guccione et al demonstrated the effectiveness of correcting visual defects via the Femto-LASIK procedure among 31 patients. These researchers noted a correction of the preoperative astigmatic topographic cylinder of 56% and of the preoperative refractive error of over 42%, as well as an approximate 20% improvement in BCVA and UCVA values [ 41 ]. Chuprov et al also confirmed the safety and effectiveness of the Femto-LASIK procedure during the correction of astigmatism while operating on cataracts among a group of patients for whom the implantation of toric intraocular lenses or peripheral femtolaser corneal incision were used.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Guccione et al demonstrated the effectiveness of correcting visual defects via the Femto-LASIK procedure among 31 patients. These researchers noted a correction of the preoperative astigmatic topographic cylinder of 56% and of the preoperative refractive error of over 42%, as well as an approximate 20% improvement in BCVA and UCVA values [ 41 ]. Chuprov et al also confirmed the safety and effectiveness of the Femto-LASIK procedure during the correction of astigmatism while operating on cataracts among a group of patients for whom the implantation of toric intraocular lenses or peripheral femtolaser corneal incision were used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional intervention is required in cases of contact lens failure brought on by corneal irregularity, lens intolerance, dry eye, and issues with manual dexterity [ 9 ]. This includes incisional keratotomy, wedge resection, laser refractive surgeries, intracorneal segments, and intraocular lens (IOL) implantation [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two phases can be distinguished after a corneal transplant: the "plastic phase", usually during the first 6 to 8 months after surgery, when the sutures are still in place and astigmatism can be managed by the modulation of their tension due to the transplant scar plasticity, and the "static phase" in which all sutures have been taken out, the graft scar has solidified, and the corneal architecture is no longer capable of considerable change [11].…”
Section: Introductionmentioning
confidence: 99%